Fingerprints as an Index for Cooperation in Children during Dental Treatment: A Cross-sectional Study - Meera, A. K.; Punathil, Sameer; Pai, Archana; James, Jeswin; Venugopal, Jipsa; Rag, Bimal (Kerala Dental Journal, 2024)
Abstract Background: The behaviour of a child is an essential factor in paediatric dentistry. Fingerprints are unique and constant over a lifetime. Some studies indicate a relationship between fingerprint type and behaviour mode of children during dental treatment. Therefore, fingerprint patterns might help to predict the extent of cooperation by children during dental procedures. Aim: The aim of the study was to investigate the possible relationship between fingerprint patterns and the cooperation of children during dental procedures. Materials and Methods: In this cross-sectional study, 80 children aged 4-7 years were examined. The children meeting the inclusion criteria in their first dental visit are scheduled for a dental procedure. During this procedure, based on Frankl's scale, the child's behaviour is assessed. Subjects were categorised as cooperative or uncooperative. A different examiner records the child's fingerprint. The data were compared with SPSS Version 21. Intergroup comparison was made using the Chi-square test at a significance level of P < 0.05. Results: Amongst the 47 cooperative children, 34 children had loop fingerprint pattern, 7 had whorl fingerprint pattern and 6 had arch fingerprint patterns. Amongst the 33 uncooperative children, 14 had loop fingerprint pattern, 15 had whorl fingerprint pattern and 4 had arch fingerprint pattern. The difference was significant between the groups (P < 0.01) based on dermatoglyphic characteristics, with the loop pattern being seen in cooperative children and the whorl pattern in uncooperative children. Conclusion: There is a relationship between fingerprint type and behaviour mode of children, with loop pattern being the primary fingerprint type amongst the cooperative group and whorl pattern amongst the uncooperative group.